Estrogen directly stimulates LHb expression at the pituitary level during puberty in female zebrafish. (5th February 2018) - Li, Gaofei; Tang, Haipei; Chen, Yu; Yin, Yike; Ogawa, Satoshi; Liu, Meifeng; Guo, Yin; Qi, Xin; Liu, Yun; Parhar, Ishwar S.; Liu, Xiaochun; Lin, Haoran
Abstract: The LHb expression is up-regulated during puberty in female zebrafish. However, the molecular mechanism underlying how LHb expression is regulated during puberty remains largely unknown. In this study, we found that the mRNA expression levels of lhb, fshb and cyp19a1b were up-regulated along with the puberty onset in zebrafish. Among the three nuclear estrogen receptors (nERs), the esr2b is the only type whose expression is significantly up-regulated during puberty onset in the pituitary. However, in situ hybridization results revealed that lhb mRNA was colocalized with esr1 and esr2a but not esr2b . Exposure to estradiol (E2 ) significantly stimulates LHb expression in both wild-type and kiss1 −/− ; kiss2 −/− ; gnrh3 −/− triple knockout pubertal zebrafish. Moreover, exposure of cultured pituitary cells to E2 increased the LHb expression, indicating that the estrogenic effect on LHb expression could be acted at the pituitary level. Finally, we cloned and analyzed the promoter of lhb by luciferase assay. Our results indicated that the E2 responsive regions of lhb promoter for ERα and ERβ2 are identical, suggesting that ERα and ERβ2 could bind to the same half ERE region of the promoter of lhb, exhibiting a classical ERE-dependent pathway. In summary, we demonstrate that E2 could directly act on the pituitary level to stimulate LHb transcription during puberty in zebrafish. Highlights: E2 could act on the pituitary level to stimulate LHb expression during puberty in female zebrafish. E2 exposure to kiss1 −/− ; kiss2 −/− ; gnrh3 −/− KO line showed that the estrogenic effect on LHb did not rely on KISS/GnRH systems. lhb mRNA was found to be colocalized with ERα and ERβ2 in the pituitary glands of early pubertal female zebrafish. For the first time in teleosts, we studied the estrogenic effects on lhb promoter activity through all lhb -colocalized nERs.